(untitled) (Research, Society and Development, 2022)
The process of occupation of agricultural areas in the state of Rondônia occurred in a disorderly way, increasing the fragility of ecosystems, due to partial and/or total suppression of native vegetation. The objective of this work was to analyze the soil cover of the Enganado river microbasin, between the years 1984 to 2021. The Enganado river watershed covers about 218 rural enterprises. For the analysis, the QGIS 2.18.0 software, images from the Landsat 5 (1984, 1988 and 2008) and Landsat 8 (2021) satellites were used. Next, three classes were stratified (native forest, agriculture and water resource - water) with the “slicer” tool, and conversion of the generated image in matrix to vector format, with the polygonize tool. The classification of the images was done with the “Graduated Style” tool, and later manual adjustments were carried out in the classes. To delimit the riparian zone, the “buffer” tool was used under variable distance, considering the fiscal modules, as established in the relevant legislation. There was a percentage reduction of the native forest class from 63.73% to 31.77% of the total area, and an amplification of the agricultural class from 33.26% to 68.05%, in the period from 1984 to 2021, the water class , in turn, was distinguished only in the years 2008 and 2021 with 0.14% and 0.16%, respectively. Approximately 584 ha of environmental liabilities were measured. There is a need to recover permanent preservation areas for environmental regularization.